Engineering-scale application of sulfur-driven autotrophic denitrification wetland for advanced treatment of municipal tailwater. (July 2023) - Li, Yingying; Han, Qi; Li, Bang
Graphical abstract: Highlights: SADN successfully operated in 1800 m 3 /d engineering-scale constructed wetland. SADN-VFCW effectively improve N and P removal in municipal tailwater. Sulfur modification induced the variation of bacterial community structure. Autotrophic denitrifying bacteria were significantly enriched by sulfur padding. Abstract: An engineering-scale sulfur driven autotrophic denitrification vertical-flow constructed wetland (SADN-VFCW) was established to treat low C/N ratio tailwater from municipal wastewater treatment plants (MWTPs). One-year stable operation results indicated that the addition of sulfur prominently enhanced TN, NO3 – -N and TP removal with efficiencies higher than 68.9%, 69.2% and 45.5%, respectively. Higher nitrogen and phosphorus removal rates were achieved in summer than that in other seasons. Furthermore, the microbial analysis revealed the structure of the microbial community changed significantly after sulfur addition, which proved that sulfur promoted the enrichment of autotrophic ( Thiobacillus, Sulfurimonas, Ferritrophicum ) and heterotrophic ( Denitratisoma, Anaerolineaae, Simplicispira ) functional bacteria, thus facilitating pollutants removal. Function prediction analysis results also indicated the abundance of nitrate removal/sulfur metabolism functions was significantly strengthened. This study achieved reliable engineering-scale application of SADN-VFCW and offered great potential for simultaneous in-depth treatment of N and P in municipal tailwater by SADN system.